2012
DOI: 10.1186/1423-0127-19-34
|View full text |Cite
|
Sign up to set email alerts
|

The role of thrombomodulin lectin-like domain in inflammation

Abstract: Thrombomodulin (TM) is a cell surface glycoprotein which is widely expressed in a variety of cell types. It is a cofactor for thrombin binding that mediates protein C activation and inhibits thrombin activity. In addition to its anticoagulant activity, recent evidence has revealed that TM, especially its lectin-like domain, has potent anti-inflammatory function through a variety of molecular mechanisms. The lectin-like domain of TM plays an important role in suppressing inflammation independent of the TM antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 55 publications
(69 reference statements)
2
73
0
Order By: Relevance
“…Additional evidence supporting the anti-inflammatory effects of THBDD1 comes from the decreased HMGB1 protein levels in HG mediumcultured podocytes that were treated with rTHBDD1. This observation is consistent with findings that HMGB1 and receptors for AGE are blocked by THBDD1, thereby inhibiting a NG (5 mmol/l) HMGB1-mediated inflammatory reactions [25]. Increased serum levels of THBD domains have been observed in patients with diabetes [31][32][33] and some specific forms of THBD domains were differentially expressed in patients with DN and non-diabetic nephritis [33]; however, the role of THBD in these renal conditions was not determined.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Additional evidence supporting the anti-inflammatory effects of THBDD1 comes from the decreased HMGB1 protein levels in HG mediumcultured podocytes that were treated with rTHBDD1. This observation is consistent with findings that HMGB1 and receptors for AGE are blocked by THBDD1, thereby inhibiting a NG (5 mmol/l) HMGB1-mediated inflammatory reactions [25]. Increased serum levels of THBD domains have been observed in patients with diabetes [31][32][33] and some specific forms of THBD domains were differentially expressed in patients with DN and non-diabetic nephritis [33]; however, the role of THBD in these renal conditions was not determined.…”
Section: Discussionsupporting
confidence: 79%
“…This finding is confirmed by our recent observation, in a mouse model of sepsis, that THBDD1 has APC-independent anti-inflammatory activity in vivo and inhibits neutrophil infiltration into the kidney [15]. Collectively, ours and several lines of research have suggested possible mechanisms for the direct anti-inflammatory effects of THBDD1, including: (1) interference with the binding of lipopolysaccharide to its receptor and inhibition of inflammatory mediator production by macrophages [15]; (2) suppression of adhesion molecule expression by neutrophils acting via the NF-κB and MAPK pathways [24]; (3) prevention of leucocyte activation by sequestration of HMGB1 protein [25]; and (4) interference with complement activation (C3a and C5a) via the classical and lectin pathways [26]. In addition, our previous study showed that anti-inflammatory effects can significantly ameliorate DN in db/db mice [7] by blocking the NF-κB-mediated inflammatory pathway.…”
Section: Discussionmentioning
confidence: 99%
“…According to our review of the previous literatures ( Table), the prognosis of patients demonstrating HL associated with HLH is extremely poor. In our case, the initial administration of chemotherapy with CHOP actually resulted in deterioration of HLH, even producing DIC, while the admini- stration of steroids and rTM was effective in managing the patient's clinical course, possibly through potent antiinflammatory functions (41). The therapeutic approach to treating advanced stage HL is controversial.…”
Section: Discussionmentioning
confidence: 91%
“…Thrombomodulin (TM) is an endothelial anticoagulant cofactor that promotes thrombin-mediated formation of activated protein C [109] . TM plays an anti-inflammatory role through inactivation of HMGB1 [109,110] . Recombinant human soluble TM (rTM) has recently become available [111] , and this novel drug is effective for sepsis [110] .…”
Section: Injurymentioning
confidence: 99%